A pilot trial of moderated online social therapy for family and friends of young people with borderline personality disorder features. Issue 6 (1st December 2020) - Gleeson, John; Alvarez‐Jimenez, Mario; Betts, Jennifer K.; McCutcheon, Louise; Jovev, Martina; Lederman, Reeva; Herrman, Helen; Cotton, Susan M.; Bendall, Sarah; McKechnie, Ben; Burke, Emma; Koval, Peter; et al.
Abstract: Aim: We evaluated the acceptability, usability and safety of Kindred, a novel online intervention for carers of young people with borderline personality disorder (BPD) using a pre–post pilot trial design. The secondary aim explored whether Kindred use was associated with clinical improvements for caregivers on measures of burden of caregiving, stress, expressed emotion, family communication, disability, coping and knowledge of BPD and for patients on measures of severity of BPD symptoms and level of functional impairment. Methods: The trial site was the Helping Young People Early program for young people with BPD at Orygen in Melbourne, Australia. Informed consent was obtained from 20 adult carers (i.e., relatives or friends) and 10 young people aged 15–25 with BPD. Kindred, which was available for 3 months, incorporated online psychoeducation, carer‐to‐carer social networking and guidance from expert and peer moderators. Assessments were completed at baseline and 3 months follow‐up. Multiple indicators of acceptability, usability and safety were utilized. Results: Seventeen carers were enrolled in Kindred and eight young people completed baseline measures. A priori acceptability, usability and safety criteria were met. Carer burden, stress, expressed emotion, family communication, quality of life, functioning, coping and perceived knowledge of BPD improved at follow‐up. Sixty‐six percent of the young people (4/6) reported that they believed Kindred had improved their carers' understanding of BPD. Conclusion: Kindred was shown to be acceptable, usable and safe, with encouraging improvements in both carer and young person outcomes. Kindred warrants evaluation of its efficacy via an randomized controlled trial.